PERFORMANCE ANALYSIS AND LIGHTWEIGHT DESIGN OF A FRONT SUBFRAME - JIANG LiHong; WU QingJie (Jixie qiangdu)
Aiming at checking the performance of a front subframe whether could meet the design requirements.Firstly,the grid model of the front subframe was built by adopting finite element method,and it was modal performance analyzed,the analysis result showed that its first two natural frequency were higher than the engine excitation frequency,so it could meet dynamic performance requirements.Secondly,the front subframe was modal tested,the test result showed that its simulation analysis precision was high.Thirdly,the front suspension dynamic model was built,and it was load based on theoretical forces,so its connection point load of typical working condition were obtained.Fourthly,the front subframe was strength analyzed by adopting inertia release method,the analysis result showed that its stress were lower than material yield value,so it could meet meet the strength characteristics.Lastly,the front subframe was lightweight designed by adopting neighborhood cultivation multiobjective genetic algorithm,the optimal thickness were obtained.Its modal performance and strength performance could meet the requirements after optimization,its weight had been successfully reduced by 9.9%,and it had passed the real vehicle road test verification.The theoretical and scientific reference were provided for obtaining the structural performance and optimization design.